Pain and discomfort following immediate and delayed loading by overdentures in the single mandibular implant study (SMIS) - Mundt, Thomas; Passia, Nicole; Kappel, Stefanie (Clinical oral investigations, 2017)
ObjectivesThis randomized clinical trial compares immediate and delayed loading of single implants to support mandibular overdentures. The aim of this preliminary analysis is to test the hypothesis whether patients with immediate loading will experience less pain and discomfort through the intervention than patients with delayed loading.Materials and methodsEdentulous patients in nine German dental schools received a midline implant with a length of 11 mm. Implants with a minimum insertion torque of 30 Ncm and an implant stability quotient of ≥60 were randomly allocated to group A for immediate loading using ball attachments or to group B for delayed loading after 3 months. Patients completed questionnaires with 100-mm visual analogue scales about the items pain, pain during chewing, swelling, bleeding, and perception of the intervention at the day of surgery and 1, 2, 3, and 7 days, thereafter. Groups were compared by Wilcoxon-Mann-Whitney tests (P ≤ 0.05).ResultsThe questionnaires of 81 patients in group A and 74 patients in group B were completed. The medians for pain and discomfort were moderate (<30). Participants of group A felt significantly more pain from the first day and more swelling from the third day after implantation than participants of group B. The individual perception of interventions showed no significant differences between groups.ConclusionsImmediate loading evoked more postoperative pain and swelling than the two stages of delayed loading.Clinical relevanceImmediate loading of a single mandibular midline implant supporting overdentures should be carefully considered.